Different Approaches to Islamic Medicine in Iran - Jafari, Ali; Parizi, Mohammad Sohrabian (Jurnal Medis Islam Internasional, 2023)
Background: Subject and objectives: Using the capabilities of Islamic civilization is one of the topics that has attracted the attention of contemporary Islamic thinkers. In this context, various opinions have been presented about whether medicine is Islamic or not among Iranian thinkers. In this article, we seek to examine the negative and positive opinions about the nature of Islamic medicine. The purpose of this article is to find a precise definition of Islamic medicine and provide a correct solution in using this treatment model. Result: This research deals with the study of Islamic medicine through descriptive-analytical and documentary methods. In this research, a complete search of electronic banks, related books, and internet sites was conducted and all acceptable articles were reviewed completely and systematically. There are different views on the nature of Islamic medicine, each of which has looked at the issue from its own angle, some agree with it and some oppose it. Conclusion: Islamic medicine has very good capacities, although there are serious criticisms against it. Islamic medicine is a specialized science, and a common opinion should be reached about its limits and conditions, and a system should be designed and drawn for it. The revival of Islamic medicine will contribute to the development of the modern Islamic civilization.